Burnout e estratégias de enfrentamento em jogadores de futebol profissionais e amadores - Verardi, Carlos Eduardo Lopes (2008)
Stress and coping have an important impact on professional practice. Objective: To identify burnout levels and coping strategies used by professional and amateur football players during the pre-competitive season. Participants were 134 male football players, 71 professionals (16 to 34 years; mean age 22.77; SD: 3.98) and 63 amateurs (15 to 18 years; mean age:17.18; SD:0.84) from three teams participating on the First Division State Championship. Method: During Series A-1 and A-2 of the Paulista Championship (professionals) and São Paulo Cup of Junior Football (amateurs) players who agreed to participate signed a consent form. They filled a charter questionnaire about demographic data, and answered the Burnout Athletes Questionnaire (QBA), and the Coping with Problems Scale (EMEP). For data analysis descriptive statistics, test for comparison of two proportions, t test for comparing means of independent samples, mean test and Mann-Whitney non parametric test were used. Significance level was P<0.05. Results: There was no significant difference (P<0.05) between both categories of athletes (professional and amateur) according to the means of the burnout sub-scales. Neither time length as athlete (professional or amateur) nor game position influenced the presence of burnout symptoms in the three categories. However, professional goalkeepers and attack players and amateur defenders presented higher mean scores for burnout associated with physical and emotional exhaustion. There were no significant differences related to coping strategies used by players (problem focused, emotion focused, wishful thinking/religious practices, and social support). Coping Focused Problem was the most frequently strategy used by all players (amateurs: mean=3.77 and professionals:mean=3.78). On the other hand, social support was the least used coping strategy (professionals: mean=1.94 and amateurs: mean=2.13). When coping strategies were compared based on game position and player category (professional or amateur), lateral player amateurs used more wishful thinking /religious practices (P=0.042) than professionals. Conclusions: There were no significant differences on the three burnout dimensions between both categories of football players, even when different game positions were considered. Coping Focused Problem was the most used strategy used by both the professionals and amateurs, except the amateur laterais, who used more wishful thinking /religious practices.